The new HR : how to beat the competition with a strategically focused human resources team - Spina, James D.; Spina, Lori J. (Emerald points., 2022)
HR departments endeavour to occupy strategic roles in organizations, a goal that is seldom or ever realized. James and Lori Spina bring their academic and corporate backgrounds together to analyse and direct on how strategic human resources cohesively contribute towards gaining competitive advantage, above average profits, building and retaining talent, sustaining financial strength, and addressing challenges of stakeholder satisfaction. Stepping beyond unclear discussions about strategy that fail to satisfy the needs of all departments, The New HR instead illustrates how human resource leaders can constructively create and nurture teams that think strategically and produce harmony between HR activities and the wider organization. The New HR is essential reading for human resources executives who desire to make strategic business decisions that ensure the sustainability and growth of the organization and, at the same time, look for new ways to develop the business, strategic, and critical thinking skills of current employees.